(untitled) (مجلة الواحات للبحوث والدراسات, 2023)
ملخص: تهدف هذه الدراسة إلى معرفة أثر البرامج التنموية على تنمية الموارد المائية بولاية ورقلة باعتباره موردا مهما لتحقيق التنمية والاستقرار وتوفير الحاجيات الضرورية للإنسان من الماء الشروب وتنمية الأنشطة الزراعية لتوفير الأمن الغذائي ، الأنشطة الصناعية والسياحية، فتم التطرق إلى برامج الإنعاش الاقتصادي (2001-2004)، برنامج المخططات الخماسية (2005-2019) التي تم تنفيذها على المستوى المركزي و اللامركزي من حيث المحتوى والأهداف، حيث قمنا بدراسة تطور وضعية الموارد المائية بولاية ورقلة من خلال عرض أهم الانجازات المحققة بتنفيذ مشاريع البرامج القطاعية، المخططات البلدية للتنمية، والصندوق الخاص لتطوير مناطق الجنوب وقد تبين أن البرامج التنموية حققت نتائج إيجابية في بعض الجوانب، لكنها لم تصل إلى المستوى المطلوب، مقارنة بالأغلفة المالية المرصودة. كلمات دالة: برامج تنموية، موارد مائية، برنامج قطاعي PS، مخططات بلدية للتنمية PCD صندوق تنمية مناطق الجنوب FSDRS، ورقلة. Abstract: The Study Aims At Arriving At The Effect Of Developmental Programs On Water Supply In Ouargla. Considering It An Important Sector To Provide Stability And Continuous Development In That The Program Counts On Supplying Necessary Drinkable Water, Developing The Agricultural Sector By Providing Food Security. In Addition, The Program Accounts For Developing The Industrial Activities Such As Factors, Petroleum. Then, We Touch On Various Economic Recovery Programs (2001/2004), A Five Year Plan Program (2005/2019) That Were Executed At Centralized And Decentralized Levels Inasmuch As Content And Goals Are Concerned. We Also Attempted To Evaluate The Development Of The Water Supply Sector In Ouargla Citway By Exposing The Paramount Results Concerning Execution Of City Hall Programs, South Sponsorship. The Study Concluded That Developmental Programs Achieved Promising Results In Some Aspects. In Others However, They Haven’t Been As Expected To Be, Especially Taking Into Account The Amount Of Supply Dedicated To Enhancements. Key Words: Developmental Programs, Water Resources, Sector Program, Communal Development Plan, Special Fund For The Development Of The South, Ouargla .